2022
DOI: 10.1186/s43161-022-00091-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional progressive resistance exercise versus eccentric muscle control in children with hemiplegia: a randomized controlled trial

Abstract: Background Historically, strength exercise in children with CP is not recommended, because it may develop spasticity, which results in difficulty with walking. But, recently increasing studies and systemic reviews have reported that strength exercise can promote muscle strength in children with CP with no negative impact on spasticity. The study is aiming to compare the effect of functional resistance exercise and functional eccentric training on dynamic balance and functional ability in childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The results of the study female college students after exercise intervention, the balance area of the test group increased substantially, and the control group decreased slightly, proving that exercise is important for enhancing the balance ability of female college students. Studies have demonstrated that exercise is beneficial in improving functional capacity and dynamic balance in children with hemiplegia (Soliman et al, 2022), a randomized controlled trial showed that a gait training program used by stroke patients was beneficial in improving balance (Shaw et al, 2022), and another study female university students through 8 weeks of fitness qigong exercises. The result was a significant increase in balance test scores post-intervention compared to pre-intervention scores (Su et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study female college students after exercise intervention, the balance area of the test group increased substantially, and the control group decreased slightly, proving that exercise is important for enhancing the balance ability of female college students. Studies have demonstrated that exercise is beneficial in improving functional capacity and dynamic balance in children with hemiplegia (Soliman et al, 2022), a randomized controlled trial showed that a gait training program used by stroke patients was beneficial in improving balance (Shaw et al, 2022), and another study female university students through 8 weeks of fitness qigong exercises. The result was a significant increase in balance test scores post-intervention compared to pre-intervention scores (Su et al, 2018).…”
Section: Discussionmentioning
confidence: 99%